Tr1 Cells as a Key Regulator for Maintaining Immune Homeostasis in Transplantation - Song, Yun; Wang, Ning; Chen, Lihua; Fang, Liang (Frontiers in Immunology, 2021)
The immune system is composed of effectors and regulators. Type 1 regulatory T (Tr1) cells are classified as a distinct subset of T cells, and they secret high levels of IL-10 but lack the expression of the forkhead box P3 (Foxp3). Tr1 cells act as key regulators in the immune network, and play a central role in maintaining immune homeostasis. The regulatory capacity of Tr1 cells depends on many mechanisms, including secretion of suppressive cytokines, cell-cell contacts, cytotoxicity and metabolic regulation. A breakdown of Tr1-cell-mediated tolerance is closely linked with the pathogenesis of various diseases. Based on this observation, Tr1-cell therapy has emerged as a successful treatment option for a number of human diseases. In this review, we describe an overview of Tr1 cell identification, functions and related molecular mechanisms. We also discuss the current protocols to induce/expand Tr1 cells in vitro for clinical application, and summarize the recent progress of Tr1 cells in transplantation.